Stunting Intervension Strategy Based on Community Empowerment - Meutia, Intan Fitri; Yulianti, Devi (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
The problem of stunting is still spread in various parts of the world including Indonesia which is a developing country with diverse community conditions. Lampung Province which is one of the regions with a high prevalence of stunting. This research is about the strategy intervention of stunting cases in Lampung Province through Asah, Asih and Asuh programs based on community empowerment. The focus of this research is on the stunting intervention strategy through Asah, Asih and Asuh program to the community. The research approach used descriptive qualitative type. The data analysis techniques used data reduction, data display and conclusion. There were some informants for this research such as the Head of the family and nutrition health section, Head of the Program and Data Evaluation Division, Head of the Health Services and Stakeholders Division. They were the keys informants. We picked ten to be interviewed. We decided to use purposive sampling to decide the informants. This study showed that the stunting intervension strategy was still weak because of some reasons such as 1). The program has not yet been performed on specific nutrition interventions from Lampung Provincial Health, 2). The human resources indicators have less ability in carrying out the Asah, Asih and Asuh programs and decision makers in formulating legislation for reducing stunting cases and 3). There is the cooperation among stakeholders to accelerate nutrition improvement activities in handling stunting.